Factors Associated With Cryptosporidium Infection Among Adult HIV Positive Population in Contact With Livestock in Namwala District, Zambia - Sinyangwe, Ntazana N.; Siwila, Joyce; Muma, John B.; Chola, Mumbi; Michelo, Charles (Frontiers in Public Health, 2020)
Cryptosporidium spp. is one of the leading causes of diarrhoeal disease globally. In Zambia, the burden of Cryptosporidium infection in the general human population is unknown and factors associated with it are unclear. A study was conducted to determine the prevalence of Cryptosporidium spp. and identify factors associated with its infection among Human Immunodeficiency Virus (HIV) positive individuals in contact with livestock in Namwala district of Zambia. Three hundred and twenty six stool samples were collected from HIV infected individuals presenting at local health centers in Namwala district of Zambia between August 2015 and June 2016. The Meriflour Cryptosporidium/Giardia test kit was used to test for presence of oocysts. Demographic information such as age and sex and information on hypothesized risk factors was collected using a structured questionnaire. Overall prevalence of Cryptosporidium infection was 9.5% (95% CI = 6.7–13.2%); 13.3% and 7.1% among male and female participants, respectively. Males were 2.5 times more likely to be infected than females whereas the divorced had higher odds of being infected (OR = 14.8). Participants who kept animals had a higher prevalence (11.4%) than those that did not (7.0%). Those that shared water with neighbors were 5.7 times more likely to be infected than those who did not. We conclude that Cryptosporidium infection is prevalent among HIV positive adults in Namwala district and infection is associated with sex, marital status and sharing water sources among neighbors. Community sensitization is required to create awareness and reduce human exposure to Cryptosporidium infection.